Adherencia al tratamiento antirretroviral en pacientes adultos con VIH-SIDA: una revisión sistemática de alcance - Díaz Gallegos, Kelly Leonela (2024)
HIV/AIDS infection continues to be a pathology of great impact on public health worldwide, being the lack of adherence to antiretroviral treatment one of the main problems faced by patients with this infection. For this reason, the present systematic review aimed to characterize adherence to antiretroviral treatment in adult patients with HIV-AIDS, in the dimensions of degree of adherence and risk factors. Regarding the methodology, the protocol was constructed under the PRISMA ScR guidelines and the JBI manuals; the search for information was conducted in the Scielo, PubMed, LILACS and Dialnet databases, identifying a total of 227 articles, of which 211 publications were excluded because they did not meet the eligibility criteria and finally 14 studies were included in this research. From the studies that were collected, it was found that, in most of the articles, more than half of the study population were adherent to antiretroviral treatment; while in others, it was identified that most of the study population were not adherent, and in relation to the risk factors associated with nonadherence, the following were found: factors related to the therapeutic regimen (adverse reactions; comorbidities; longer time under treatment), factors related to the individual (stress, depression, stigma, forgetfulness, consumption of psychoactive substances and alcohol, academic grade, male sex and younger age) and factors related to the social situation (lack of family social support). In conclusion, the lack of adherence to antiretroviral treatment is a latent problem that was highlighted in the scientific evidence analyzed; in view of this, factors related to the individual, the social situation and those related to the therapeutic regimen are strongly linked to this problem